Implementation of Teaching Media for EFL Learning at Post – Pandemic - Sukma, I Made Gunawan Adi; Nitiasih, Putu Kerti; Agustini, Dewa Ayu Eka (Universitas Pendidikan Ganesha, 2023)
One of the instruments that instructors may utilize to support the educational process at school is teaching media. Teachers can employ various instructional resources, including audio, visual, and audiovisual-based material. Some teachers continue using teaching media for various reasons, while others do not. This study aims to analyze teaching media teachers use in post-pandemic English language learning at senior high school. A case study methodology and a qualitative approach were both employed in this investigation. Three teachers chosen by the researcher served as the study's informants. Interviews and checklist observational methods were employed as data-gathering strategies. Data analysis used Miles & Huberman's theory, for data validity uses triangulation. The results of this study show that implementing teaching media can make it easier for teachers to deliver information and can also make it easier for students to receive information. This study's findings include Teacher's use of laptops, LCD projectors, active speakers, headsets, and the use of language laboratory rooms in listening activities. In addition, there are several obstacles experienced by teachers in implementing each media, such as the need for teacher adaptation to ICT developments and facility factors that are only sometimes ready to be used.